The SECCA procedure for faecal incontinence: a review. (March 2014) - Frascio, M.; Mandolfino, F.; Imperatore, M.; Stabilini, C.; Fornaro, R.; Gianetta, E.; Wexner, S. D.
Abstract Aim The SECCA system is a treatment option for patients with faecal incontinence and was introduced into clinical practice in 2002. Clinical studies of radiofrequency energy to treat patients with faecal incontinence have been published. This article aimed to review all published series to assess the results of this treatment. Method Twelve studies were included. Outcomes analysed included quality of life, the Wexner incontinence score, anorectal manometry and endoanal ultrasound findings. Results A total of 220 patients from 10 studies were included. In the majority of clinical studies, the SECCA procedure has been shown to be an effective treatment of mild‐to‐moderate faecal incontinence. Conclusion When patient selection is appropriate, this treatment has demonstrated clinically significant improvements in symptoms, as demonstrated by statistically significant reductions in the Wexner incontinence and quality of life scores.